“Andamos todo o ano a trabalhar para a festa”: festa e dádiva no bodo de Monfortinho - Chambino, Eddy (Trabalhos de Antropologia e Etnologia, 2020)
The main intention of this work is to share a research itinerary, in the form of a report of the Bodo de Monfortinho. The formal framework is based on the lines of work of the Raiano Cultural Center / Idanha-a-Nova Municipality and as an ongoing project, here it is presented as a moving, experiential text, still mediated by the search for directions in the uncertain search for the heritage values .